(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Rogalskaya N. V. Using projects in the training of future specialists preschool education. The paper addresses the problem of improving the professional training of preschool education specialists, in particular in use in the educational process of higher education project method.